2016
DOI: 10.7172/2353-6845.jbfe.2016.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Investor Flows and Sovereign Bond Yields in Advanced Economies

Abstract: Asset allocation decisions of international investors are at the core of capital fl ows. This paper explores the impact of these decisions on long-term government bond yields, using a quarterly investor base dataset for 22 advanced economies over 2004-2012. We fi nd that a one percentage point increase in the share of government debt held by foreign investors can explain a 6-10 basis point reduction in long-term sovereign bond yields over the sample period. Accordingly, international fl ows to core advanced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…There is some evidence that an increase in foreign investors reduces sovereign bond yields in advanced economies (e.g. Andritzky, 2012;Arslanalp and Poghosyan, 2014). This is confirmed in the single-country literature on the United States, which finds a negative effect of the rise in global investors on US Treasury securities and long-term sovereign bond yields (Beltran et al, 2012;Warnock and Warnock, 2009).…”
Section: Market Responsivenessmentioning
confidence: 66%
“…There is some evidence that an increase in foreign investors reduces sovereign bond yields in advanced economies (e.g. Andritzky, 2012;Arslanalp and Poghosyan, 2014). This is confirmed in the single-country literature on the United States, which finds a negative effect of the rise in global investors on US Treasury securities and long-term sovereign bond yields (Beltran et al, 2012;Warnock and Warnock, 2009).…”
Section: Market Responsivenessmentioning
confidence: 66%
“…Utility maximizing portfolio models incorporates preference for kurtosis, kinked utility functions in which investors favor or dislike skewness and kurtosis. 6 See Andritzky (2012), Arslanalp and Poghosyan (2014), Gray (2013), Reinhart and Rogoff (2011), and Tagkalakis (2014).…”
Section: Choice Of the Variables And Related Literaturementioning
confidence: 98%
“…However, Neely (2015) focused on the crisis period from 2008 to 2009 and Rogers et al (2018) employed the UK, the whole euro area, and Japan as a sample, which are excluded from our sample period and countries, respectively. 39 Arslanalp and Poghosyan (2016) suggested that an increase in the share of government debts held by foreigners related to a reduction in long-term government bond yields of advanced economies. Similarly, we conducted the estimation that exhibits the change in the foreign shares of government bond markets as an independent variable.…”
Section: Inoguchimentioning
confidence: 99%
“…between our results and that of Arslanalp and Poghosyan is the difference in sample periods and countries. Arslanalp and Poghosyan (2016) employed the regression period 2004-2011 and 22 advanced economies including G7 and euro area countries, which are different from our sample period and countries. 40 We also implement the test using conditional logit model to check the influence of country fixed effects.…”
Section: Inoguchimentioning
confidence: 99%